2020
DOI: 10.3390/ijerph17238809
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Personality for Objective and Subjective-Physical Health in Older Men and Women

Abstract: Objective and subjective health generally have a positive relationship, although their association may be moderated by factors such as gender and personality. We aimed to analyze the association between personality and objective (metabolic syndrome (MetS)) and subjective-physical health in older men and women. For this purpose, in 138 participants (53.6% women, Mage = 66.85), neuroticism, conscientiousness, extraversion, openness, and agreeableness (NEO Five Factor Inventory), subjective-physical health (Short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…A final strength is that we accounted for personality which is also an important factor affecting subjective ratings of health. [31][32][33] Turning to the findings, we observed lower incidence rate ratios for 'Excellent' self-reported health some four decades later among children who had high caries experience than among those who were caries-free at 5 years old. This was despite some differences between the cohorts in terms of the numbers represented in the moderate and high caries groups, and differences in the wording of the self-rated general health questions used; however, findings were not significant in either cohort.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…A final strength is that we accounted for personality which is also an important factor affecting subjective ratings of health. [31][32][33] Turning to the findings, we observed lower incidence rate ratios for 'Excellent' self-reported health some four decades later among children who had high caries experience than among those who were caries-free at 5 years old. This was despite some differences between the cohorts in terms of the numbers represented in the moderate and high caries groups, and differences in the wording of the self-rated general health questions used; however, findings were not significant in either cohort.…”
Section: Discussionmentioning
confidence: 70%
“…Another strength was the inclusion of important covariates known to affect oral health. A final strength is that we accounted for personality which is also an important factor affecting subjective ratings of health 31–33 …”
Section: Discussionmentioning
confidence: 99%
“…Our results were in line with the study of Sutin et al ( 42 ) who observed that young adults with higher neuroticism had a greater risk of elevated BP. Similarly, it has been reported that high neuroticism was more likely to induce metabolic syndrome in women than in men ( 68 ). Although extraversion, conscientiousness, or agreeableness was shown to be beneficial for BP in other studies, these favorable relationships between BP and other personality traits were not observed in our study.…”
Section: Discussionmentioning
confidence: 76%
“…На сьогодні зафіксовано, що поліпшення санітарно-гігієнічних умов та умов життя людей, що розпочалося в XIX столітті, сприяло колосальному підвищенню рівня здоров'я і збільшенню тривалості життя [2]. Ці поліпшення дозволили успішно боротися з інфекційними захворюваннями й повністю позбавити сучасне © 2021.…”
Section: вступunclassified